Improving Customer Service Quality through the Utilization of Google Suites in Landing Page Creation - Purwanto, Moch. Edy; Hasanah, Herliyani; Purwanto, Eko (Jurnal Ekonomi, 2024)
This research investigates the utilization of Google Suites for enhancing customer service quality through the creation of landing pages. Landing pages play a crucial role in digital marketing by capturing visitors' attention and converting them into customers or leads. Leveraging Google Suites, including tools such as Google Sites, Google Forms, and Google Analytics, offers organizations a comprehensive platform for designing, deploying, and analyzing landing pages to better serve their customers. Through a thorough examination of scholarly articles and relevant publications, this research synthesizes existing literature to explore the benefits and challenges of utilizing Google Suites for landing page creation. It delves into case studies and practical examples to provide insights into how organizations can effectively leverage Google Suites to optimize landing page design, personalize customer experiences, gather valuable feedback through forms, and analyze performance metrics using analytics tools. Moreover, the study examines the impact of improved landing page quality on customer satisfaction, engagement, and retention. By employing quantitative methodologies, this paper offers critical insights into the potential of Google Suites as a valuable resource for enhancing customer service quality in the digital age. It underscores the importance of integrating technology-driven solutions into customer service strategies to meet the evolving needs and expectations of today's consumers. The findings contribute to advancing understanding of the role of technology in customer service excellence and provide practical implications for organizations seeking to leverage Google Suites for effective landing page management.